2018
DOI: 10.1021/acs.orglett.8b02537
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Dehydrogenating Coupling of Aldehydes with Amines/R-OTBS Ethers by Visible-Light Photoredox Catalysis: Synthesis of Amides, Esters, and Ureas

Abstract: A straightforward synthesis of amides, ureas, and esters is reported by visible-light cross-dehydrogenating coupling (CDC) of aldehydes (or amine carbaldehydes) and amines/R-OTBS ethers by photoredox catalysis. The reaction is found to be general and high yielding. A plausible mechanistic pathway has been proposed for these transformations and is supported by appropriate controlled experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 103 publications
(38 reference statements)
2
39
0
Order By: Relevance
“…Notably, 5 was produced by the reaction of BHT with singlet oxygen generated by the anthraquinone photocatalyst under visible light irradiation conditions (Scheme ). The results of this experiment indicated that the reaction was not mediated by the photocatalytically generated singlet oxygen, as previously reported in the literature . As already mentioned, anthraquinone is known and used as a catalyst for the production of hydrogen peroxide .…”
Section: Methodssupporting
confidence: 87%
“…Notably, 5 was produced by the reaction of BHT with singlet oxygen generated by the anthraquinone photocatalyst under visible light irradiation conditions (Scheme ). The results of this experiment indicated that the reaction was not mediated by the photocatalytically generated singlet oxygen, as previously reported in the literature . As already mentioned, anthraquinone is known and used as a catalyst for the production of hydrogen peroxide .…”
Section: Methodssupporting
confidence: 87%
“…Interestingly, amide formation was also observed without the addition of DIPEA (Table , entry 7). This reaction occurred because piperidine can donate a single electron to PC and thereby forms a piperidine radical, which may attack the carbonyl bond of the aldehyde and subsequent proton abstraction by O 2 .− produced the amide . Air in place of O 2 provided a diminished yield (Table , entry 8).…”
Section: Methodsmentioning
confidence: 99%
“…This reactiono ccurred because piperidine can donate as ingle electron to PC and therebyf orms ap iperidine radical, which may attack the carbonyl bond of the aldehyde and subsequent proton abstraction by O 2 C À produced the amide. [25] Air in place of O 2 providedadiminished yield (Table 1, entry 8). The use of eosin Y, rose bengal,a nd [Ru(bpy) 3 ] 2 + (bpy = 2,2'-bipyridine) as aP Cf ailed to produce amide 1 (Table 1, entries 9-11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…29 It has seen numerous applications in atom-transfer radical addition (ATRA) reactions, both photochemically 30,31 or by classical radical methods [32][33][34][35] and also as an oxidizing agent; used directly, [36][37][38] or within a photoredox catalytic cycle. [39][40][41][42] It was anticipated that by utilizing advancements in light source and reactor technology, an improved methodology could be developed. Accordingly, the advantages of simple separation of a single by-product (CHCl 3 ), highly concentrated reactions without precipitation of solid reagents and the possibility of accessing electron-rich benzyl bromides may be realized (Scheme 1).…”
mentioning
confidence: 99%